3D manufactured, water-powered soft actuators for orthodontic application. (12th July 2018) - Hsu, Hao; Liu, Liang-Yen; Liu, Ling-Ying; Su, Yu-Chuan
Abstract: Soft actuators with embedded power sources are critical for applications where space is limited but safety and functionality are demanded. We have successfully demonstrated (1) a 3D design/fabrication/packaging scheme that can readily upgrade conventional hydraulic actuators into autonomous osmotic actuators, and (2) integrated soft actuators that can yield desired locomotion and force outputs for orthodontic application. Flexible composite structures with semipermeable interfaces are employed to realize the desired actuation, including elongation, contraction, bending, and twisting. More specifically, thin-walled polymer bellows are utilized to control and amplify the actuation caused by osmosis. In the prototype demonstration, 25 mm long soft bellow structures with outer diameters up to 4 mm and wall thicknesses down to 250 μ m were designed, 3D printed, shrink wrapped with semipermeable membranes, assembled, and characterized. When placed in aqueous media, the actuators were osmotically pressurized to function in steady and preprogrammed manners. The constant water flow rate across the semipermeable interface (with an effective working area of 30 mm 2 ) into each presented osmotic actuator was measured to be 156 μ l h −1, while the inner pressure can reach 200 kPa in few hours. It was demonstrated that both the inner/outer pressure difference and locomotion/force outputs are proportional to the actuation time. When applied on teeth, the osmotic actuators are expected to steadily overcome the rising resistance from surrounding tissues, and therefore achieve constant-rate and long-lasting movement of teeth. In addition to pumping, it is demonstrated for the first time that osmotic actuation can be tailored to accomplish sophisticated locomotion functions.